Legal Review of Hoaxes on Social Media in the Post-Truth Era - Iskandar, Farid; Faozi, Ahmad Afif (Generate Digital Publishing, 2025)
Objective: This research analyses the phenomenon of spreading hoaxes on social media in the context of the post-truth era, where false information spreads more easily and influences public opinion compared to objective facts. Focusing on a legal perspective, this study analyses the regulations and rules that apply in Indonesia regarding the spread of fake news (hoaxes) and their legal impact on the perpetrators. Research Design & Methods: This research uses a normative juridical approach through literature study, with doctrinal analysis of regulations on hoaxes on social media and the views of legal experts regarding their application in the post-truth era. Findings: The results show that although legal tools are in place, implementation challenges and low digital literacy are still hindering, so multi-stakeholder collaboration and increased digital literacy education are needed as long-term solutions to reduce the spread of hoaxes in the post-truth era. Implications & Recommendations: Law enforcement against hoaxes requires cross-sector collaboration, increased digital literacy, regulatory updates, and synergy between law enforcement and digital platforms for fast and effective handling. Contribution & Value Added: This research makes an important contribution by examining the role of law in addressing hoaxes in the post-truth era and suggests multi-stakeholder collaboration and regulatory updates for more effective handling of hoaxes on social media.